Prognostic value of HLA-A2 status in advanced non-small cell lung cancer patients. (October 2017) - Mezquita, Laura; Charrier, Melinda; Faivre, Laura; Dupraz, Louise; Lueza, Béranger; Remon, Jordi; Planchard, David; Bluthgen, Maria Virginia; Facchinetti, Francesco; Rahal, Arslane; Polo, Valentina; Gazzah, Anas; et al.
Highlights: HLA-A2 was positive in 48% of the patients, consistent with previous studies. No association between HLA-A2 and patient or tumor characteristics. No prognostic role for HLA-A2 in advanced NSCLC population. Abstract: Introduction: The class I human leucocyte antigen (HLA) molecules play a critical role as an escape mechanism of antitumoral immunity. HLA-A2 status has been evaluated as a prognostic factor in lung cancer, mostly in localized disease and with inconsistent findings. We evaluated the role of HLA-A2 status as a prognostic factor in a large and homogeneus cohort of advanced NSCLC patients. Methods: Advanced NSCLC patients eligible for platinum-based chemotherapy were consecutively included in a single center between October 2009 and July 2015 in the prospective MSN study (NCT02105168). HLA-A2 status was analysed by flow cytometry. Clinical, pathological and molecular data were collected. A Cox model was used for prognostic analyses. Results: Of 545 stage IIIB/IV NSCLC patients included, 344 (63%) were male, 466 (85%) were smokers, 447 (83%) had PS 0–1, 508 (93%) had stage IV, 407 (75%) had an adenocarcinoma and median age was 61 years (range, 21–84). Incidence of patients with EGFRmut, ALK -positive and KRASmut was 14% (49/361), 9% (29/333) and 31% (107/350), respectively. The overall rate of HLA-A2 positivity was 48%. No association was observed between HLA-A2 status and any patient or tumor characteristics analyzed. With a median follow-up of 27.1 months, median OS was 12.8 months [95%CI 11.0–14.6] in HLA-A2+ vs. 12.5 months [95%CI 10.4–15.3] in HLA-A2- patients (HR 1.05 [95%CI 0.86–1.29], p = 0.61). Median progression-free survival was similar in the two cohorts. Conclusion: HLA-A2 status was not identified as prognostic for benefit in a large advanced NSCLC population treated with platinum-based chemotherapy.